The innovative use of artificial intelligence in the arbitral tribunal: Malaysian perspective - Labanieh, Mohamad Fateh; Hussain, Mohammad Azam (Science and Engineering Research Support Society, 2020)
-Arbitration is one of the mechanism for dispute resolution in Malaysia. This institution is not new and works as a complementary to the court system. The current arbitration institution still applying the traditional method in hearing the arbitral process. With the current development of technology, it seems that the adoption of new technology into this institution needs to be considered. Especially preparing this institution facing the era of IR4.0. Artificial intelligence is one of the tool which need to be addressed in the arbitration system. Is it possible to use the artificial intelligence as an arbitrator in hearing process? Whether the existing arbitration framework in Malaysia is ready to adopt such artificial intelligence? This article seeks to scrutinize the using of artificial intelligence into arbitration processes. Also to examine whether the existing arbitration framework is ready to use artificial intelligence in handling disputes especially the legal fraternity. By using library research methodology, this study found that, a lot of advantages of using artificial intelligent in arbitration processes. However in order to adopt artificial intelligent in this institution, several loopholes of the current arbitration framework need to be improved especially the legal aspect. Artificial intelligence able to work as a complimentary to the existing arbitration framework.